Messengers From the Gut: Gut Microbiota-Derived Metabolites on Host Regulation - Li, Chenyu; Liang, Yaquan; Qiao, Yuan (Frontiers in Microbiology, 2022)
The human gut is the natural habitat for trillions of microorganisms, known as the gut microbiota, which play indispensable roles in maintaining host health. Defining the underlying mechanistic basis of the gut microbiota-host interactions has important implications for treating microbiota-associated diseases. At the fundamental level, the gut microbiota encodes a myriad of microbial enzymes that can modify various dietary precursors and host metabolites and synthesize, de novo, unique microbiota-derived metabolites that traverse from the host gut into the blood circulation. These gut microbiota-derived metabolites serve as key effector molecules to elicit host responses. In this review, we summarize recent studies in the understanding of the major classes of gut microbiota-derived metabolites, including short-chain fatty acids (SCFAs), bile acids (BAs) and peptidoglycan fragments (PGNs) on their regulatory effects on host functions. Elucidation of the structures and biological activities of such microbiota-derived metabolites in the host represents an exciting and critical area of research.